Android applications development for image and video processing - Choo, Ryan Tze Hao (Nanyang Technological University, 2022)
The smartphone has become a necessity today [1]. There is an estimate of 6.378 billion smartphone users in 2021 [2], with an estimate of 1.43 trillion photographs taken from smartphones in 2020 alone. Such a large number of photographs taken in just one year would provide an increase in demand for image processing applications. Furthermore, with the growing number of people using social media websites such as e.g. (Instagram and TikTok), the number of photos taken will only skyrocket further. Avid photographers would seek out the use of filters and image beautifiers to better express themselves through their photographs. Hence, image processing applications are slowly becoming ingrained and becoming more and more popular. Expression is an Android Based mobile application that is designed to tackle such problems faced by users. Expression offers many functions which will be discussed extensively in this report. The main features of this application would be accessing the device camera or selecting an image from the gallery, and processing this image based on the user’s preference, which will be then saved in the gallery. After image processing, the user will have a choice of sharing the newly processed image through any applications available on the device (e.g., Facebook, Twitter, WhatsApp, Gmail).